Overview of inner rotor radial permanent magnet machines for electric vehicles. Issue 1 (September 2020) - Ali Soomro, Irfan; Sulaiman, Erwan; Jenal, Mahyuzie; Ali, Hassan
Abstract: Nowadays, there is fast growing interest in electric vehicles from automakers, governments and customers due to increasing concern of our environment. This paper presents an overview of various inner rotor radial permanent magnet electric machines for application to electric vehicles (EVs). First of all, the classification and brief introduction of radial permanent magnet machines are presented. The key features of the machines, including the advantages and disadvantages of the machines are summarized. Furthermore, the latest development of the machines is also reviewed. Then, the structure of viable electric machines that have been applied to electric vehicles, including radial permanent magnet synchronous machines (PMSM), switched reluctance (SRM), interior permanent magnet (IPM) and flux switching machines (FSM) types are being reviewed.